2010
DOI: 10.4137/jen.s4104
|View full text |Cite
|
Sign up to set email alerts
|

Local cell proliferation upon enucleation in Direct Retinal Brain Targets in the Visual system of the Adult Mouse

Abstract: In this study we used incorporation of the DNA synthesis marker 5-bromo-2′-deoxyuridine or BrdU to visualize cell proliferation in the visual system of the adult mouse as a response to monocular enucleation. We detected new BrdU-labeled cells in different subcortical retinal target regions and we established a specific time frame in which this cell proliferation occurred. By performing immunofluorescent double stainings for BrdU and different vascular (glucose transporter type 1, collagen type IV), glial (thym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 108 publications
(150 reference statements)
0
4
0
Order By: Relevance
“…At the cellular level, a glial response prevails across different subcortical direct retinal target structures in the adult mouse upon ME, as an early marker of neuronal injury (Cuyvers et al, 2010 ). Instant denervation-induced microglial activation precedes astrogliosis mainly in contra- but also in ipsilateral subcortical structures, including the LGN and SC (Wilms and Bähr, 1995 ; Gonzalez et al, 2006 ).…”
Section: Monocular Enucleation As a Brain Plasticity Modelmentioning
confidence: 99%
“…At the cellular level, a glial response prevails across different subcortical direct retinal target structures in the adult mouse upon ME, as an early marker of neuronal injury (Cuyvers et al, 2010 ). Instant denervation-induced microglial activation precedes astrogliosis mainly in contra- but also in ipsilateral subcortical structures, including the LGN and SC (Wilms and Bähr, 1995 ; Gonzalez et al, 2006 ).…”
Section: Monocular Enucleation As a Brain Plasticity Modelmentioning
confidence: 99%
“…Through its involvement in actin metabolism, the peptide is implicated in processes like motility, synaptogenesis and growth of neuronal processes (Carpintero et al 1999;Gomez-Marquez and Anadon 2002;Van Kesteren et al 2006;Vartiainen et al 1996;Yang et al 2008), as well as in glial activation that occurs after brain damage (Cuyvers et al 2010;Dong et al 2005;Kim et al 2006;Vartiainen et al 1996). Indeed, actin polymerization is a crucial event for cellular motility, axonal path finding and synaptogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, Yoshida et al (2002) found an up-regulation in the kidney in an ischemiareperfusion model. We recently also reported an up-regulation of Tb4-immunoreactive microglia in all direct retinal target structures of the brain, including the superficial layers of the superior colliculus (SC), after monocular enucleation in the adult mouse (Cuyvers et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Reactive oxygen species, which function as messenger molecules to mediate structural remodeling, were also detected in subcortical structures of the adult rat visual system 14 . Furthermore, microglial and astroglial activation across different subcortical visual target structures in the mouse occur in a specific post-enucleation time frame of one week 15 . Together, optic deafferentation results in different subcortical responses at the glial, structural and molecular level.…”
Section: Introductionmentioning
confidence: 99%